If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7a + 9 = 3a + 40 Reorder the terms: 9 + -7a = 3a + 40 Reorder the terms: 9 + -7a = 40 + 3a Solving 9 + -7a = 40 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. 9 + -7a + -3a = 40 + 3a + -3a Combine like terms: -7a + -3a = -10a 9 + -10a = 40 + 3a + -3a Combine like terms: 3a + -3a = 0 9 + -10a = 40 + 0 9 + -10a = 40 Add '-9' to each side of the equation. 9 + -9 + -10a = 40 + -9 Combine like terms: 9 + -9 = 0 0 + -10a = 40 + -9 -10a = 40 + -9 Combine like terms: 40 + -9 = 31 -10a = 31 Divide each side by '-10'. a = -3.1 Simplifying a = -3.1
| 0=42X+18X^2-2X^3 | | 43x+5=9 | | 9m-1-2m=6m-1-m | | 2y=-2x-2 | | 11(-2a+2b-3c)-9(5a-6b+2c)=0 | | 13=-8-5d | | 3(4d-3)-2d=-4 | | -2x-2y=2 | | 4X^2-6X=7-6X | | W^2+60w-4000=0 | | -4x+3[5(x+7)-3x+2]=7(x+5) | | -35+11= | | 18x+3=12x | | 215-4x=32x+19 | | 3h+8=16 | | 11+-35= | | 2x+3x-85+20=180 | | 15+10x=3-6x | | 12x^2+5x-2=o | | 5m+4m=54 | | 9n^2+79=18n | | 5(4-6h)=8(6h-4) | | h=50/20 | | -5c-2c+12=5 | | s^2+4s+25=0 | | 3d=4 | | 2(4x+2)+2(2x)=2(4x)+2(4x) | | -3/4=m/22 | | 9/2=k/25 | | 4.14-3(2.6x-5)=6.9x-(x-1) | | 8x+80=180 | | 6-3b=-18 |